2013
DOI: 10.1080/21553769.2014.881304
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic effects ofEmbelia ribesextract in high fat diet and low dose streptozotocin-induced type 2 diabetic rats

Abstract: Embelia ribes is extensively used in the traditional Indian system of medicine for treatment of various disorders. We herein investigated the antidiabetic effects of E. ribes ethanolic extract in high fat diet (HFD) and low dose streptozotocin (STZ)-induced type 2 diabetes in Wistar rats. HFD-fed and low dose STZ (35 mg kg −1 , i.p)-induced diabetic rats were treated with E. ribes extract (100 and 200 mg kg −1 day −1 ) or metformin (180 mg kg −1 day −1 ) for 21 days while continuing on HFD. Antihyperglycemic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…High glucose levels were stored in the liver and muscle tissue with the help of insulin using a glucose transporter. As a result, the hepatic glycogen content in the HFD/STZ-induced diabetic control group signifi cantly reduced (P<0.05) compared to the normal control group, which was indicative of tissue insulin resistance [Bhandari et al, 2013]. Treatment with MVR and glibenclamide would be able to restore glycogen content indicating tissue glucose uptake and hepatic glucose production [Moore et al, 2012].…”
Section: Discussionmentioning
confidence: 94%
“…High glucose levels were stored in the liver and muscle tissue with the help of insulin using a glucose transporter. As a result, the hepatic glycogen content in the HFD/STZ-induced diabetic control group signifi cantly reduced (P<0.05) compared to the normal control group, which was indicative of tissue insulin resistance [Bhandari et al, 2013]. Treatment with MVR and glibenclamide would be able to restore glycogen content indicating tissue glucose uptake and hepatic glucose production [Moore et al, 2012].…”
Section: Discussionmentioning
confidence: 94%
“…Despite the presented literature revealed that β-cells have the ability to regenerate, however, controversies are still existing [52,53]. The partial destruction of β-cells by the small dose of streptozotocin to high fat fed rats has been claimed to induce T2D by lowering insulin secretion coupled with insulin resistance [23,54]. The significantly lower level of serum insulin in T2D control rats indicted the partial destruction of pancreatic β-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of Embelia Ribes ethanolic extract to diabetic rats produced considerable reduction in serum lipase activity, that suggests its potential in prevention of lipid abnormalities and obesity (Bhandari et al 2013). 11 Ethanolic extract of Embelia Ribes has shown lipid lowering potential in terms of decrease serum total cholesterol, and triglycerides, and increase in HDLcholesterol levels in streptozotocin induced diabetes in rats after twenty days of oral administration at the dose of 200 mg/kg compared to pathogenic diabetic rats (Bhandari et al 2012). 12 Pretreatment with embelin (50 mg/kg) significantly decreased the elevated levels of serum lipid levels and lipoproteins in high fat diet induced obese rats (Chaudhari HS et al).…”
Section: Effects Of Embelia Ribes On Dyslipidemiamentioning
confidence: 99%